SOCIO-ECONOMIC DETERMINANTS OF BIRTH AND EMERGENCY PREPAREDNESS IN ANTENATAL CARE: A STUDY AMONG MOTHERS IN THE WA MUNICIPALITY - Yelkumo, N. Y.; Suara, S. B.; Boakye-Yiadom, A.; Aryee, P. A. (UDS International Journal of Development, 2019)
Inadequate birth and emergency preparedness are a recipe for the development of complications that often lead to morbidities and mortalities during pregnancy and child birth. Yet, little is known of the socio-economic factors that affect birth and emergency preparedness in the Wa Municipality. Therefore, the objective of the study was to assess the socio-economic determinants of birth and emergency preparedness among mothers with children up to one year of age. A facility based cross sectional study was employed to get information from respondents. The sampling technique used was multistage sampling and a structured questionnaire was used as the data collection instrument. Logistic regression was used to identify the determinants of birth and emergency preparedness. A total of 401 mothers participated in the study. It was revealed that 43.4% of respondents were knowledgeable in pregnancy danger signs. About 62% were adequately prepared for birth. In multivariate analysis, mothers who: had attained at least secondary education (P< 0.001), had high wealth index (P< 0.001), had at most 2 children (P=0.035), had four or more ANC visits (P=0.003) were significantly more likely to prepare adequately for birth. The above variables stood out as the major socio-economic determinants of birth and emergency preparedness. The study showed that birth and emergency preparedness among mothers in the study setting occurs in the context of specific socio-economic factors that are likely to mould the behaviours of women towards preparing adequately for birth preparedness and emergency services uptake. There is therefore the need for all stakeholders in the area of health to work towards reinforcing these variables or determinants to ensure women are adequately prepared for birth and emergencies. Keywords: Birth Preparedness, Socio-Economic Determinants, Ante-Natal Care, Pregnancy Complications, Maternal Mortality Rate